2(x+1)+5=-7(x+1)-13

Simple and best practice solution for 2(x+1)+5=-7(x+1)-13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(x+1)+5=-7(x+1)-13 equation:


Simplifying
2(x + 1) + 5 = -7(x + 1) + -13

Reorder the terms:
2(1 + x) + 5 = -7(x + 1) + -13
(1 * 2 + x * 2) + 5 = -7(x + 1) + -13
(2 + 2x) + 5 = -7(x + 1) + -13

Reorder the terms:
2 + 5 + 2x = -7(x + 1) + -13

Combine like terms: 2 + 5 = 7
7 + 2x = -7(x + 1) + -13

Reorder the terms:
7 + 2x = -7(1 + x) + -13
7 + 2x = (1 * -7 + x * -7) + -13
7 + 2x = (-7 + -7x) + -13

Reorder the terms:
7 + 2x = -7 + -13 + -7x

Combine like terms: -7 + -13 = -20
7 + 2x = -20 + -7x

Solving
7 + 2x = -20 + -7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '7x' to each side of the equation.
7 + 2x + 7x = -20 + -7x + 7x

Combine like terms: 2x + 7x = 9x
7 + 9x = -20 + -7x + 7x

Combine like terms: -7x + 7x = 0
7 + 9x = -20 + 0
7 + 9x = -20

Add '-7' to each side of the equation.
7 + -7 + 9x = -20 + -7

Combine like terms: 7 + -7 = 0
0 + 9x = -20 + -7
9x = -20 + -7

Combine like terms: -20 + -7 = -27
9x = -27

Divide each side by '9'.
x = -3

Simplifying
x = -3

See similar equations:

| 4/=3.6 | | 45=9(5c+12) | | 3m^2=30+13m | | 37=130/x | | 28-9x=3 | | -7f+6=166+3f | | 2x-(13)=3 | | 2/3x^2-1/3=0 | | z=2z-70 | | (4x)(-3xy^2)= | | (4x+9)-(x+9)=33 | | -(12-x)=4 | | 3x+2(6x-4)=52 | | 3x+20=8x-4 | | x^2=22+3x | | -5c-12/4=2 | | 4x+5(-5x+9)=171 | | (3x-5)+(3x+5)=180 | | 9(3x+10)-20x=2x+115 | | -6j+7=8j-16j-13 | | m/16-3=(-2) | | 4a/3=10 | | -8(p+2)+p=4(p+3)+5 | | 5x+7=50 | | -x-14=1 | | 3y+8y-19=17+5y | | 10/60=x/100 | | 12-2(4x-5)=-2 | | 35=6v-5+4v | | 6(2x-1)+2(x+11)=2 | | X/x^4/24 | | (5x/2)-9=(2x-7/6) |

Equations solver categories